Notes on the prices of Irish agricultural produce illustrated by diagrams - Barrington, Richard M. (Statistical and Social Inquiry Society of Ireland, 1893)
The paper on this subject I had the honour of reading before the Society, in December, 1886, was based on statistics derived from private sources. The following notes and diagrams are, on the other hand, compiled and drawn from data which are, for the most part, public property. To speculate on the causes which affect prices, or discuss the remedies which have been, from time to time, applied or suggested to counteract their fall or check their rise, is outside the scope of this paper. Agricultural values only are dealt with, the figures and authorities are given. As far as possible, the great question of agricultural depression has been avoided. For some products the quotations extend backwards over a century.
Read Wednesday, 1st March, 1893
Keywords: Agricultural prices; Agricultural produce; 314.15